Assessment of microbial communities in PM1 and PM10 of Urumqi during winter. (July 2016) - Gou, Huange; Lu, Jianjiang; Li, Shanman; Tong, Yanbin; Xie, Chunbin; Zheng, Xiaowu
Abstract: Recently, inhalable particulate matter has been reported to carry microorganisms responsible for human allergy and respiratory disease. The unique geographical environment and adverse weather conditions of Urumqi cause double pollution of dust and smog, but research on the microbial content of the atmosphere has not been commenced. In this study, 16S and 18S rRNA gene sequencing were conducted to investigate the microbial composition of Urumqi's PM1 and PM10 pollutants in winter. Results showed that the bacterial community is mainly composed of Proteobacteria, Firmicutes and Actinobacteria, Proteobacteria accounted for the most proportion which was significant difference in some aforementioned studies. Ascomycota and Basidiomycota constitute the main part of the fungal microbial community. The difference of bacterial relative abundance in sample point is greater than in particle sizes. The sequences of several pathogenic bacteria and opportunistic pathogens were also detected, such as Acinetobacter, Delftia, Serratia, Chryseobacterium, which may impact on immunocompromised populations (elderly, children and postoperative convalescence patients), and some fungal genera may cause several plant diseases. Our findings may serve an important reference value in the global air microbial propagation and air microbial research in desert. Highlights: Using 16 s rDNA double variable region (V3 + V4) sequencing to elucidate the bacterial communities. Several potential microbial allergens and pathogens present in PM1 and PM10 were found. Providing a great supplement to environmental science and human health assessment.